Thermal and optical properties of high-density GaN micro-LED arrays on flexible substrates. (July 2020) - Asad, Mohsen; Li, Qing; Sachdev, Manoj; Wong, William S.
Abstract: Flexible GaN-based micron-size light-emitting diodes (μLEDs) with high brightness and low power-consumption are a promising technology for next-generation wearable displays. While, integrating GaN μLEDs onto flex can provide more functionality, the bending-induced strain and potential self-heating of the device are the challenges that degrade the device performance on plastic platforms. Here, a novel "paste-and-cut" approach to selectively transfer GaN μLEDs from sapphire substrates onto flexible platforms demonstrated the effectiveness of various intermediate metallic-bonding layers and LED geometries on the optical properties and performance of the flexible devices. Computational thermal simulation of the flexible μLEDs showed effective heat dissipation for devices mounted on plastic platforms bonded using a 0.5 μm thick Cu metallic pad to create stable optical emission (λ = 450 nm) under current densities of >1 A/cm 2 . Through a finite-element analysis (FEA), it was determined that the applied stress-induced strain near the quantum wells of the μLEDs can be negligible for devices with diameters smaller than 20 μm. Experimental verification supported the simulation results; the diodes were found to be electrically and thermally stable when copper electrode layers >600 nm thick was used to bond the LEDs onto the plastic platforms. The I–V characteristics of the μLEDs showed no measurable degradation after transfer onto the flexible substrate with a turn-on voltage of 2.5 V. Commensurate to the FEA simulations, no measurable optical wavelength shift was observed for LED having a diameter of 20 μm when driven at a current density of 1 A/cm 2 under different mechanical strain. Graphical abstract: The following figures plot the pack emission shift and the calculated device temperature integrated on various substrates and also the electroluminescence intensity measured under mechanical bending. The scanning electron microscopy image of the high-resolution micro-LED arrays integrated on the flexible substrate is shown on the left side. Image 1 Highlights: The flexible micro-LEDs mechanical strain and self-heating effects are investigated as challenges in flexible displays. Numerical modeling is developed to propsed an optimized geometry and structure. A novel "paste-and-cut" approach is demonstrated for selectively transferring micro-LEDs on flex and verifying the theory. The EL of the 20 µm diameter micro-LEDs showed no measurable degradation under the mechanical bending. The self-heating of the micro-LEDs on flex was addressed by integration devices onto copper electrodes thicker than 600 nm.